Immediate effects of cold on balance and proprioception in Thai healthy older adults - Sirinun Boripuntakul (Journal of Associated Medical Sciences, 2017)
Background: Cold has been commonly used to treat musculoskeletal injuries, especially in acute stage. However, there were some studies demonstrated that cold is temporarily affected on decreasing balance and proprioceptive performance in young adults which contribute to falling.